Simulasi Penyerapan Tenaga Kerja dengan Pendekatan Demometrik - Esti R, Hedwigis; Brodjonegoro, Bambang P. S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2003)
Labor absorption hardly depends on the economic capacity and in the absence of market imperfection, the labor will be allocated efficiently among sectors. However, the assumption is hardly found in reality, and this give us a space to identify the explanatory variable of labor absorption. This research analyzes the sectoral labor absorption based on J. Ladent model that internalize the demographic variable together with economic variable. We apply this model to analyze the sectoral labor absorption in Cental Java using annual basis data from 1978-1999, and simulate the sectoral labor absorption under three different scenarios; quo, optimist and pessimist scenario. The result shows labor absorption is highly correlated to labor quality, economic capacity and investment. Based on simulation, we find that any shock on demographic or economic variable yield unequal impact on labor absorption across sector. We find strong causality between GDP and national unemployment, and labor absorption. We also conform the lack of foreign capital investment as the main source of in-optimal leading sector development.